Between Faith and Science: The Role of Hadith in Challenging Covid-19 Protocols in Indonesia - Abdul Haris; Nurul Afifah (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study aims to analyse how hadiths have been employed as means to delegitimize health protocol policies during the performance of prayer, including the use of masks, spacing of rows (saf), praying at home, and even mosque closures—a phenomenon that has received limited attention in hadith studies, particularly in the context of the Covid-19 pandemic. Adopting a constructivist approach, the study employs two levels of analysis: descriptive and critical, drawing data from social media platforms such as YouTube, Instagram, WhatsApp, and Facebook. The findings show substantial variation in the media type, source, and quality of the hadiths employed. The interpretations of the hadith largely fall into two categories: simplistic and literalist–translationist. Both modes of understanding are prone to specific cognitive patterns: (1) authoritarianism and irrationality, and (2) romanticization of the past coupled with religious egoism. Collectively, these results underscore a pronounced polarization between “hadith” and “science.”